2004
DOI: 10.1037/0022-3514.86.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Self-Verification Motives at the Collective Level of Self-Definition.

Abstract: Three studies examined self-verification motives in relation to collective aspects of the self. Several moderators of collective self-verification were also examined-namely, the certainty with which collective self-views are held, the nature of one's ties to a source of self-verification, the salience of the collective self, and the importance of group identification. Evidence for collective self-verification emerged across all studies, particularly when collective self-views were held with high certainty (Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 55 publications
11
114
3
6
Order By: Relevance
“…We have noted that these findings apply to collective aspects of the self (social identity) as well. At an intragroup level, our review suggests that being treated as a proper member of the in-group by in-groupers seems to be necessary to maintain one's identity (see e.g., Chen et al, 2004;Klein et al, 2005;Noel et al, 1995). Identity performance indeed seems to be used to generate such confirmatory reactions from audiences.…”
Section: Conclusion: From Identity Performance To Identity Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have noted that these findings apply to collective aspects of the self (social identity) as well. At an intragroup level, our review suggests that being treated as a proper member of the in-group by in-groupers seems to be necessary to maintain one's identity (see e.g., Chen et al, 2004;Klein et al, 2005;Noel et al, 1995). Identity performance indeed seems to be used to generate such confirmatory reactions from audiences.…”
Section: Conclusion: From Identity Performance To Identity Constructionmentioning
confidence: 99%
“…A long tradition of research on interpersonal relations testifies to the existence of this motivation for "self-verification" (Swann, 1983(Swann, , 1987, which seems to generalize to collective aspects of identity as well (Chen, Chen, & Shaw, 2004). Conversely, it has long been shown that people strategically use their self-presentations to establish positive interpersonal relationships.…”
Section: The Identity Consolidation Functionmentioning
confidence: 99%
“…One way to understand defensiveness and security at the level of the collective self is to first consider these processes at the level of the individual self (e.g., Bizman, Yinon, & Krotman, 2001;Chen, Chen, & Shaw, 2004). Personal defensiveness can be seen as a selffavouring bias linked to a need for approval, allegedly stemming from "deep-seated" frustrations (Cramer, 1998;Deci & Ryan, 2000;Schneider & Turkat, 1975).…”
Section: Security and Defensiveness In The Self And The Groupmentioning
confidence: 99%
“…Reis et al (2004) recently extended the earlier models by arguing that responsiveness to the central aspects of the self is critical to affective outcomes of social interactions. It is not surprising, then, that people like their interaction partner when the partner accurately perceives important aspects of their self-concepts (e.g., Chen, Chen, & Shaw, 2004;Swann, 1990). …”
mentioning
confidence: 99%